SOCIALIZATION OF THE IMPLEMENTATION OF TAX INCENTIVES DURING THE PANDEMIC PERIOD in BADAN USAHA MILIK DESA (BUMDES) KECAMATAN BATUJAJAR KABUPATEN BANDUNG BARAT - Purnamasari, Dyah; Mulyati, Yati; Sari, Diana; Andari, Diah; Mariana, Citra (CENTRAL ASIA AND THE CAUCASUS, 2022)
Local area Service Activities with respect to the Socialization of the Implementation of MSME Tax Incentives in the Pandemic Period In BADAN USAHA MILIK DESA (BUMDES) KECAMATAN BATUJAJAR – KABUPATEN BANDUNG BARAT. Local area Service Activities with respect to the Socialization of the Implementation of MSME Tax Incentives In BADAN USAHA MILIK DESA (BUMDES) KECAMATAN BATUJAJAR – KABUPATEN BANDUNG BARAT got an energetic reaction from BUMDes that have been completed well. BUMDes can complete the tax assessment parts of BUMDes appropriately, including the computation, installment and duty revealing accurately. BUMDes can exploit charge motivations during the COVID-19 pandemic.